Giant phagocytes (Gφ) and neutrophil-macrophage hybrids in human carotid atherosclerotic plaques – An activated phenotype - Lavie, Lena; Si-on, Erez; Hoffman, Aaron (Frontiers in Immunology, 2023)
A small subpopulation of CD66b+ neutrophils with extended lifespan and immensely large size was identified in vitro. They internalized dead neutrophil remnants and cellular debris, transforming them into giant phagocytes (Gφ) resembling macrophage-foam cells with a massive lipid content and CD68+ scavenger receptor expression. Thus, we sought to investigate if similar CD66b+ neutrophils with altered morphology and functions exist in inflammatory/atherosclerotic conditions in vivo, by using human carotid atherosclerotic plaques. Thirty-three plaques were obtained from 31 patients undergoing endarterectomy. Carotid plaques were analyzed for CD markers by immunohistochemistry and immunofluorescence and quantitatively analyzed by confocal microscopy. Intra-plaque lipids were stained with Oil Red O. Plaque CD66b+ neutrophils co-expressed myeloperoxidase (MPO)+ and neutrophil elastase (NE)+. Also, co-expression of CD66b+/CD68+, CD66b+/CD36+, CD66b+/vascular-endothelial-growth- factor (VEGF)+ and 3-nitrotyrosine (3-NT)+/NE+ was noted. Similarly, macrophages co-expressed CD163+/CD68+, CD163+/VEGF+ and CD163+/3-NT+. Both cell types were predominantly localized in lipid-rich areas and stained for lipids. CD66b+ and CD163+ expressions were highly positively correlated with each other and each with CD68+, and 3-NT+. Morphologically, CD66+ cells were big, had a rounded nucleus, and resembled macrophage-foam cell morphology as well as that of Gφ in vitro. To clarify whether CD66b+ and CD163+ cells represent two distinct plaque-populations, plaques were double-stained for CD66b/CD163 co-localization. A third of the plaques was negative for CD66b/CD163 co-localization. Other plaques had a low co-localization, but in few plaques, co-localization was high, collectively, indicating that in some of plaques there were two distinct cell populations, those resembling Gφ, and those co-expressing CD66b+/CD163+, demonstrating a hybrid neutrophil-macrophage phenotype. Interestingly, CD66b+/CD163+ co-localization was highly positively correlated with the oxidant 3-NT, hence, supporting trans-differentiation of CD66b+ cells to CD163+ Cells. Conversely, phagocytosis of dead neutrophils by macrophages might have also occurred. Thus, we conclude that in some of the plaques CD66b+ cells might represent cells resembling Gφ that developed in prolonged culture conditions. Yet, CD66b+/CD163+ co-expressing cells represent a new neutrophil-macrophage hybrid population of unknown transitioning point, possibly by adopting macrophage markers or contrariwise. Nonetheless, the significance and functions of these cells in plaque biology or other inflammatory/atherosclerotic conditions should be unveiled.